2019
DOI: 10.3390/ijms20020235
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analysis of PIN Genes in Root Tips and Nodules of Lotus japonicus

Abstract: Auxins are postulated to be one of the pivotal factors in nodulation. However, their transporters in Lotus japonicus, the model species for the study of the development of determinate-type root nodules, have been scarcely described so far, and thus their role in nodulation has remained unknown. Our research is the first focusing on polar auxin transporters in L. japonicus. We analyzed and compared expression of PINs in 20 days post rhizobial inoculation (dpi) and 54 dpi root nodules of L. japonicus by real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…It was shown that auxin transport is altered upon early stages of the symbiosis (Mathesius et al, 1998; Boot et al, 1999; Pacios-Bras et al, 2003), and that expression patterns of some PIN-encoding genes are distinct in nodule primordia (Huo et al, 2006; Sanko-Sawczenko et al, 2019). Application of gravitropic stimulation alters auxin response localization and has commonly been used in studies of lateral root emergence.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that auxin transport is altered upon early stages of the symbiosis (Mathesius et al, 1998; Boot et al, 1999; Pacios-Bras et al, 2003), and that expression patterns of some PIN-encoding genes are distinct in nodule primordia (Huo et al, 2006; Sanko-Sawczenko et al, 2019). Application of gravitropic stimulation alters auxin response localization and has commonly been used in studies of lateral root emergence.…”
Section: Discussionmentioning
confidence: 99%
“…RNA was obtained from two biological replicates of L. japonicus and M. truncatula non-inoculated roots and root nodules either subjected to drought for two (T2) or four (T4) days or well-watered control nodules (T0). Total RNA extraction was performed as described previously [ 104 ]. In the case of samples derived from root nodules, an additional rRNA subunit was observed after gel electrophoresis, which proved that, along with plant RNA, bacterial RNA had been extracted ( Figure S5 ).…”
Section: Methodsmentioning
confidence: 99%
“…cDNA synthesis was performed as described previously [ 104 ]. Real-time qPCR was performed using the Connect CFX Real-Time PCR Detection System (Bio-Rad, Hercules, CA, USA) with Power SYBR Green Master Mix (Thermo Fisher Scientific, Waltham, MA, USA) or SsoFast EvaGreen Supermix (Bio-Rad, Hercules, CA, USA) for plant or bacterial genes, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Auxin also plays a critical role in controlling the development of medicago indeterminate nodules as well as lotus and soybean determinate nodules [43,60,61]. Sanko-Sawczenko et al recently described the central role of polar auxin transport and auxin homeostasis in controlling determinate nodule development and differentiation [62].…”
Section: Introductionmentioning
confidence: 99%